Calcitriol promotes differentiation of glioma stem-like cells and increases their susceptibility to temozolomide - Gerstmeier, Julia; Possmayer, Anna-Lena; Bozkurt, Süleyman; Hoffmann, Marina E.; Đikić, Ivan; Herold-Mende, Christel; Burger, Michael C.; Münch, Christian; Kögel, Donat; Linder, Benedikt (Cancers, 2021)
Glioblastoma (GBM) is the most common and most aggressive primary brain tumor, with a very high rate of recurrence and a median survival of 15 months after diagnosis. Abundant evidence suggests that a certain sub-population of cancer cells harbors a stem-like phenotype and is likely responsible for disease recurrence, treatment resistance and potentially even for the infiltrative growth of GBM. GBM incidence has been negatively correlated with the serum levels of 25-hydroxy-vitamin D3, while the low pH within tumors has been shown to promote the expression of the vitamin D3-degrading enzyme 24-hydroxylase, encoded by the CYP24A1 gene. Therefore, we hypothesized that calcitriol can specifically target stem-like glioblastoma cells and induce their differentiation. Here, we show, using in vitro limiting dilution assays, quantitative real-time PCR, quantitative proteomics and ex vivo adult organotypic brain slice transplantation cultures, that therapeutic doses of calcitriol, the hormonally active form of vitamin D3, reduce stemness to varying extents in a panel of investigated GSC lines, and that it effectively hinders tumor growth of responding GSCs ex vivo. We further show that calcitriol synergizes with Temozolomide ex vivo to completely eliminate some GSC tumors. These findings indicate that calcitriol carries potential as an adjuvant therapy for a subgroup of GBM patients and should be analyzed in more detail in follow-up studies.
Gesehen am 14.10.2021